Answer:
[tex](AB)^T = B^T.A^T (Proved)[/tex]
Step-by-step explanation:
Given (AB )^T= B^T. A^T;
To prove this expression, we need to apply multiplication law, power law and division law of indices respectively, as shown below.
[tex](AB)^T = B^T.A^T\\\\Start, from \ Right \ hand \ side\\\\B^T.A^T = \frac{B^T.A^T}{A^T}.\frac{B^T.A^T}{B^T} (multiply \ through) \\\\ = \frac{A^{2T}.B^{2T}}{A^T.B^T} \\\\=\frac{(AB)^{2T}}{(AB)^T} \ \ (factor \ out \ the power)\\\\= (AB)^{2T-T} \ (apply \ division \ law \ of \ indices; \ \frac{x^a}{x^b} = x^{a-b})\\\\= (AB)^T \ (Proved)[/tex]